Lithium extraction by extractant confined in Pickering emulsion - Enze Li; Zelong Li; Qiancheng Xia; Feiyu Zhang; Zhangqi Liang; Zhaozan Xu; Guandao Gao; Hu Li; Fangqin Cheng (Nature Communications)
Abstract The global energy transformation towards electrification and decarbonization urgently requires a sustainable lithium supply. However, current solvent extraction technology suffers from extractant dissolution and low efficiency. Herein, we develop an oil-in-water (O/W) Pickering emulsion with high stability using amphipathic SiO2 nanoparticles to confine tributyl phosphate (TBP) extractant within the oil phase for enhancing lithium extraction from salt-lake brine. Resultantly, the Pickering emulsion achieves a lithium recovery of 91.7% with Li-Mg separation factor (β Li Mg) of 101.9 after only three-stage extraction and Li+ mass transfer rate (k) of 4.57 × 10−8 m/s, greatly outperforming the traditional TBP system (52.8% recovery, β Li Mg = 12, k = 7.50 × 10−9 m/s). We propose that the tiny gaps between SiO2 particles serve as Li+ transport channels, in which the interfacial electric field generated by surface charges of SiO2 particles and the confinement effect within these gaps synergistically enhance Li+ dehydration and diffusion.